Vitamin D deficiency in patients with tuberculosis and its correlation with glycemic status - Karoli, Ritu; Shakya, Shobhit; Singh, Prem Shanker (International Journal of Research in Medical Sciences, 2019)
Background: Comorbidity of diabetes and tuberculosis has serious health implications. Presence of diabetes at least three times increases the risk of tuberculosis which may be mediated by an abnormal innate immune response due to hyperglycaemia or low vitamin D levels. Aim of the study- Present study was carried out to investigate whether lower serum 25(OH) D might be associated with higher prevalence of pulmonary or extra pulmonary tuberculosis which might provide an evidence for a role of vitamin D in the comorbidity of these two diseases and does it have any correlation with glycemic status. Methods: In a hospital based cross sectional study, 264 patients with newly diagnosed tuberculosis were enrolled and according to glycemic status they were divided into three groups. They were assessed for vitamin D deficiency in addition to routine laboratory and biochemical parameters. Results: The patients with diabetes had significantly lower vitamin D levels. The prevalence of severe vitamin D deficiency was highest in patients who had diabetes with tuberculosis. There was negative correlation between vitamin D levels and Hba1C and extensiveness of pulmonary tuberculosis Conclusions: Serum vitamin D levels were significantly lower in tuberculosis patients with pre-diabetes and type 2 diabetes compared with those, who had normal glycemic status. We suggest that there is a need to pay more attention to vitamin D status in this country and if there is coexisting diabetes or impaired glucose intolerance, emphasis on vitamin D supplementation can be of utmost importance.